Strategi Public Relations Trans Studio Theme Park Bali dalam Pengembangan Kemitraan Sponsorship - Regina Gracia Warouw; Ni Made Prasiwi Bestari (Badan Penerbit STIEPARI Press, 2026)
Public relations has a strategic role in maintaining sustainable relationships between companies and partners that have been established through the cooperation process. However, there are still many companies that establish instant and transactional sponsorship cooperation without paying attention to long-term value and suitability to the target market. In contrast, Trans Studio Theme Park Bali implements a public relations strategy that is oriented towards the development of sponsorship partnerships in a sustainable manner. This study aims to find out how Trans Studio Theme Park Bali's public relations strategy is in developing sponsorship in order to provide reciprocal value for companies and partners. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The concept of Cutlip & Center's public relations strategy is used as an analysis technique in this study, including fact finding, planning, implementation, and evaluation. The results of the study show that Trans Studio Theme Park's public relations strategy is carried out through research on the track record of previous cooperation, value-based planning, implementation through collaborative publications in digital media, and evaluation related to feedback from partners. Thus, the strategy is carried out not only on the implementation of sponsorship, but also on the sustainability of mutually beneficial relationships and partnerships.